Analisis Kesiapan Implementasi E-Learning Menggunakan E-Learning Readiness Model - Faslah, Ronny; Santoso, Harry Budi (P3M Politeknik Negeri Banjarmasin, 2017)
The successful implementation of e-Learning in a college is influenced by many factors. One of these factors is the readiness of universities to use e-Learning in teaching and learning process. E-Learning Readiness (ELR) is an instrument developed by Aydin and Tasci to measure the level of readiness of e-Learning implementation in developing countries grouped into four factors: technology, innovation human, and self-development,. This study aims to determine the level of readiness of e-Learning implementation in teaching and learning process at Hasnur Polytechnic. The results showed that Hasnur Polytechnic is included in the ready category in applying e-learning but requires an improvement on several factors.